Impact of Pre-Hysterectomy Counseling on Depression among Patients Reffered toTUMS Hospitals - Maryam Modarres; Fatemeh Rahimikian; Abbas Mehran (Tehran University of Medical Sciences, 2013)
Background & Aim: Hysterectomy is the second most common major surgery among women of reproductive age. Studies have suggested that women do not usually receive adequate information regarding hysterectomy before the surgery. Depression is a common psychiatric condition diagnosed after hysterectomy. The aim of this study was to assess the impact of pre-hysterectomy counseling on depression among women.   Methods & Materials : In this clinical trial, 100 women who had undergone hysterectomy for non-malignant conditionswere selected from two hospitals (women's' hospital and Imam Khomeini hospital) and completed the informed consent forms. Participants were randomly divided into two intervention and control groups. In the intervention group, we implemented the supportive counseling within two sessions. Depression was assessed 1-2 weeks before the surgery and two monthsafter the surgery. Data were gathered using the 30-item SAMA questionnaire (modified BECK questionnaire in Iran)for depression and a demographic questionnaire. The two groups were assessed using the Wilcoxon rank-sum test, Mann Whitney U test and paired-t test. Data were analyzed in the SPSS-14.0. The p-value less than 0.05 was considered significant forall tests.   Results: Mann Whitney U test showed no significant difference between the control and intervention groups in the mean score of depression (p<0.001). In the intervention group, the mean score of depression was 44.46 ± 6.7 at baseline and 20.86 ± 5.9 after the intervention.   Conclusion : Pre-hysterectomy counseling should be provided for women in order to reduce negative psychological consequences.